Feasibility study on formulation of cutting fluid from waste palm oil - Yoosuf, Shabna; Maneesh, T.; Sasidharan, Baiju; Rani, S.; Ajmal, N.; Mohanan, Visakh (Recent Research in Science and Technology, 2023)
From an industrial, environmental, and scientific standpoint, the creation of renewable and sustainable products to replace fossil fuels is an important concern in this decade. Due to the growing use of different lubricant types, the majority of which are mineral-based, there is an unavoidable flow of mineral-based lubricants into the environment. Another issue is using cooking oil that pollutes the environment when discarded. Both of these issues can be resolved by creating bio-based lubricants from discarded cooking oil. This article discusses formulating a green cutting fluid made from used cooking oil. This enables the use of waste oil as a cutting fluid while retaining its tribological and environmental characteristics. In order to compete in the market, biodegradable cutting fluid might gain from decreased costs for used natural oils. The many components and trends that make up this topic are briefly covered in this article, along with waste cooking oils’ potential application as a bio-based lubricant.